Implementation of Diversion Policy for Children Who Commit Criminal Offenses: An Analysis of Effectiveness and Benefits for Children - Saragih, Imanuel; Tanjung, Andry Syafrizal; Sidi, Redyanto (JURNAL SYNTAX IMPERATIF : Jurnal Ilmu Sosial dan Pendidikan, 2025)
The ordinary legal process for children who commit crimes has some negative impacts on the child's growth and development, especially if the child has to serve a prison sentence. Therefore, the juvenile criminal justice process must prioritize the principle of restorative justice, namely by involving the perpetrator, victim, family of the perpetrator/victim, and other related parties to jointly seek a fair settlement by emphasizing restoration to the original state, and not retribution. This research aims to examine the legal policy of diversion for children who commit criminal acts and to examine in depth the benefits of diversion to legal justice for children. The type of research used is normative juridical with a descriptive-analytical approach, discussing existing legal symptoms and problems and testing them based on laws regulations, and legal norms. The results of this study show that diversion is a form of legal protection that protects the psychological, social, and mental condition of children because, through diversion, children who commit crimes can avoid the legal process by upholding restorative justice. The legal basis for diversion is regulated starting from the law, Sema, and SKB. The benefits of diversion to legal justice and benefits for children include: children do not have to comply with formal legal procedures and are not detained/imprisoned, protect children's psychological and social conditions, and anticipate the recurrence of criminal acts by children in the future.